Abnormal sterol metabolism in holoprosencephaly - Haas, Dorothea; Muenke, Maximilian (American journal of medical genetics. Part C, Seminars in medical genetics, 2010)
Holoprosencephaly (HPE) is the most common structural malformation of the developing forebrain in humans. The HPE phenotype is extremely variable and the etiology is heterogeneous. Among a variety of embryological toxins that can induce HPE, inhibitors, and other pertubations of cholesterol biosynthesis have been shown to be important factors, most likely because cholesterol is required in the Sonic hedgehog signaling cascade. Decreased levels of maternal cholesterol during pregnancy increase the risk for preterm delivery, but they are not associated with congenital malformations. However, if the fetus is affected by an inborn error of endogenous cholesterol synthesis, a reduction of maternal cholesterol concentration and cholesterol transport over the placenta aggravates the phenotypic expression. Exposure to lipophilic statins in early pregnancy may be associated with a substantial risk for structural CNS defects. © 2010 Wiley-Liss, Inc.
Gesehen am 07.06.2023